Pengembangan Perangkat Pembelajaran Fisika Berbasis Proyek untuk Meningkatkan Kemampuan Komunikasi Peserta Didik - Wiwik Kurniawati; Ahmad Harjono; Gunawan Gunawan; Ahmad Busyairi; Muhammad Taufik (Department of Physics Education, Universitas Mataram, 2021)
This study aims to determine the feasibility of project-based learning tools to improve students' communication skills. The design used is Research and Development (R&D) with a 4D model (define, design, develop, & disseminate). This research is only limited to the develop stage, namely validation by six expert validators with supporting data in the form of physics education student responses to the learning tools developed. The learning tools developed include the syllabus, lesson plans, LKPD, and observation sheet instruments. The results of the study based on expert validation showed that the learning tools developed had very valid criteria on the syllabus, lesson plans, LKPD, and observation sheet instruments. The average result of the calculation of student responses is 99%. Based on the results of these studies, it can be concluded that project-based learning tools are feasible to use in the physics learning process to improve students' communication skills.